The Use of Decision Support Systems in Social Work: A Scoping Study Literature Review. Issue 1 (2nd January 2016) - Liedgren, Pernilla; Elvhage, Gudrun; Ehrenberg, Anna; Kullberg, Christian
Abstract : Decision support systems are known to be helpful for professionals in many medical professions. In social work, decision support systems have had modest use, accompanied by strong criticism from the profession but often by praise from political management. In this study the aim of the authors was to collect and report on the published evidence on decision support systems in social work. The conclusion of the authors is that a decision support system gives support to social workers in conducting a thorough investigation, but at the same time gives them the freedom to make autonomous decisions that might be the most helpful for and used by social workers. Their results also indicate that decision support systems focusing on atypical rather than typical cases are perceived as the most useful among experienced staff.